2015
DOI: 10.1111/hepr.12612
|View full text |Cite
|
Sign up to set email alerts
|

Virological characteristics of hepatitis B genotype G/A2 recombination virus in Japan

Abstract: We found that four cases of HBV/G/A2 recombinant among MSM patients in the metropolitan areas of Japan, and HBV/A co-infections are required for its efficient replication. High-risk groups such as MSM should be carefully tested for infection of genotype G-derived variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…17 The long-term presence of different HBV genotypes in a single patient may increase the risk of recombinant strains with new clinical properties. 32 Herein, the most common recombinant HBV strain was A/G, consistent with other studies. [32][33][34] Unlike elsewhere, we also found recombinant strains with the endemic genotype H, such as H/F and H/G.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…17 The long-term presence of different HBV genotypes in a single patient may increase the risk of recombinant strains with new clinical properties. 32 Herein, the most common recombinant HBV strain was A/G, consistent with other studies. [32][33][34] Unlike elsewhere, we also found recombinant strains with the endemic genotype H, such as H/F and H/G.…”
Section: Discussionsupporting
confidence: 89%
“…32 Herein, the most common recombinant HBV strain was A/G, consistent with other studies. [32][33][34] Unlike elsewhere, we also found recombinant strains with the endemic genotype H, such as H/F and H/G.…”
Section: Discussionsupporting
confidence: 89%
“…Another study in Japan found HBV/A2 is the most frequent in HIV infected patients and is detected almost exclusively in homosexual patients (Yanagimoto et al 2012 ). Several HBV/G/A2 recombinant strains have been reported among MSM patients in Japan (Tsuzuki et al 2015 ; Kojima et al 2015 ) and all of these strains have a 36-nt insertion of the core gene. However, the insertion was not detected in the HBV/G/A2 recombinant from our patient, suggesting a possibility that he was infected with the strain outside Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination with HIV-HBV/A2 co-infection, which was frequently associated with high HBV-DNA levels, would explain his extremely high HBV-DNA level. Some studies revealed co-infection with HBV/A2 enhanced HBV/G replication (Dao et al 2011 ; Kato et al 2002a , b ; Tanaka et al 2008 ) and a in vivo study demonstrated the introduction of the HBV/A2 core promoter or core protein or both genomic regions into the HBV/G genome increased HBV/G replication efficiently (Tsuzuki et al 2015 ; Sakamoto et al 2013 ). Meanwhile, his CD4+ cell count was maintained at 226/μL, nevertheless HIV-HBV-IRIS occurred after the initiation of ART and HBV-specific CD8+ cell responses could be impaired.…”
Section: Discussionmentioning
confidence: 99%